2014
DOI: 10.1111/juaf.12066
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the City: Female Leaders and Spending on Social Welfare Programs in U.S. Municipalities

Abstract: Scholars of urban politics often argue that cities will shy away from extensive funding of social welfare programs, as fiscal realities make developmental policies far more attractive. Despite these arguments, cities continue to fund social welfare programs. One possible explanation is that some local officials prefer funding welfare programs. This research demonstrates that the presence of a female mayor has a large, positive influence on the likelihood a city participates in funding social welfare programs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 70 publications
(88 reference statements)
3
71
2
Order By: Relevance
“…One of the political agendas female politicians may pursue is to support policies that improve public service delivery and, in particular, those that improve the everyday life of women, such as family policy and health policy. It is by now rather well‐established in research on political representation that female politicians prioritise issues and policies pertaining to the situation of women in society at large to a higher degree than their male collegues (see Bolzendahl ; Bratton & Ray ; Ennser‐Jedenastik ; Holman ; Schwindt‐Bayer & Mishler ; Smith ; Wängnerud & Sundell ).…”
Section: How the Share Of Elected Female Representatives Influences Pmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the political agendas female politicians may pursue is to support policies that improve public service delivery and, in particular, those that improve the everyday life of women, such as family policy and health policy. It is by now rather well‐established in research on political representation that female politicians prioritise issues and policies pertaining to the situation of women in society at large to a higher degree than their male collegues (see Bolzendahl ; Bratton & Ray ; Ennser‐Jedenastik ; Holman ; Schwindt‐Bayer & Mishler ; Smith ; Wängnerud & Sundell ).…”
Section: How the Share Of Elected Female Representatives Influences Pmentioning
confidence: 99%
“…One of the political agendas female politicians may pursue is to support policies that improve public service delivery and, in particular, those that improve the everyday life of women, such as family policy and health policy. It is by now rather well-established in research on political representation that female politicians prioritise issues and policies pertaining to the situation of women in society at large to a higher degree than their male collegues (see Bolzendahl 2009;Bratton & Ray 2002;Ennser-Jedenastik 2017;Holman 2013;Schwindt-Bayer & Mishler 2005;Smith 2014;Wängnerud & Sundell 2012). Alexander and Ravlik (2015) transfer these findings to corruption studies, label them ʻthe women's interest mechanism' and highlight the fact that some actions by female politicians may have important spin-off effects on corruption in society at large.…”
Section: The Women's Interest Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…More varied and powerful female voices in governance would be an indirect consequence of the policy initiatives noted above, but even more direct support should come from current municipal, provincial, and federal governments where men, and especially women, need opportunities to play prominent roles in promoting gender equity. Women's voices are especially important because they often bring to governance different perspectives and values than are typically articulated by men (see, e.g., Holman ; Levi, Li, and Zhang ; also Bullough et al. ).…”
Section: Policies Moving Forwardmentioning
confidence: 99%
“…That is, it is possible if a man had requested more investments in drinking water, the result would have been the same. Holman (2014) found that the mayor's gender was a predictor for welfare spending in the United States. If the percentage of female city councillors reached 30%, there would also be an increase in spending, but female councillors were effective with a female mayor at any percentage.…”
mentioning
confidence: 99%